Local Narratives on the Adoption of Mango Integrated Crop Management Technologies in Samal Island, Philippines - Anastacio, Nico Jayson; Camacho, Jr., Jose V.; Lapitan, Aileen V.; Maquito, Ferdinand C.; Datoon, Rodmyr F.; Tanzo, Irene R.; Gapas, Jeanarah M. (Talenta Publisher, 2023)
The adoption of agricultural technologies is imperative in improving the performance of the local agriculture sector in the Philippines. Numerous technology-based development projects have been implemented across the country. The Mango ICM project was one of these interventions. It was carried out in the Island Garden of Samal, Davao del Norte (IGaCoS) with the objective of supporting the local mango industry through the promotion of environmentally sustainable technologies. Years since project completion, challenges have been raised in relation to technology adoption. To understand the adoption dynamics in IGaCoS, this study dissects the complex nature of the Mango ICM technologies and the perception and reception of the local producers towards them. This study is grounded on the narratives gathered through a series of in-depth interviews with key informants and local mango producers. Results show that although the potential benefits of the extended technologies were recognized, the existing local labor and market arrangements created barriers to technology adoption. The nature of technology, market arrangement, and financial constraints were the identified reasons for the non-adoption of the local mango producers